Impaired mechanical, heat, and cold nociception in a murine model of genetic TACE/ADAM17 knockdown. Issue 3 (26th December 2018) - Quarta, Serena; Mitrić, Miodrag; Kalpachidou, Theodora; Mair, Norbert; Schiefermeier-Mach, Natalia; Andratsch, Manfred; Qi, Yanmei; Langeslag, Michiel; Malsch, Philipp; Rose-John, Stefan; Kress, Michaela
ABSTRACT: TNF‐α‐converting enzyme, a member of the ADAM (A disintegrin and metalloproteinase) protease family and also known as ADAM17, regulates inflammation and regeneration in health and disease. ADAM17 targets are involved in pain development and hypersensitivity in animal models of inflammatory and neuropathic pain. However, the role of ADAM17 in the pain pathway is largely unknown. Therefore, we used the hypomorphic ADAM17 (ADAM17 ex/ex ) mouse model to investigate the importance of ADAM17 in nociceptive behavior, morphology, and function of primary afferent nociceptors. ADAM17 ex/ex mice were hyposensitive to noxious stimulation, showing elevated mechanical thresholds as well as impaired heat and cold sensitivity. Despite these differences, skin thickness and innervation were comparable to controls. Although dorsal root ganglia of ADAM17 ex/ex mice exhibited normal morphology of peptidergic and nonpeptidergic neurons, a small but significant reduction in the number of isolectin β‐4—positive neurons was observed. Functional electrical properties of unmyelinated nociceptors showed differences in resting membrane potential, afterhyperpolarization, and firing patterns in specific subpopulations of sensory neurons in ADAM17 ex/ex mice. However, spinal cord morphology and microglia activity in ADAM17 ex/ex mice were not altered. Our data suggest that ADAM17 contributes to the processing of painful stimuli, with a complex mode of action orchestrating the function of neurons along the pain pathway.—Quarta, S., Mitric, M., Kalpachidou, T., Mair, N., Schiefermeier‐Mach, N., Andratsch, M., Qi, Y., Langeslag, M., Malsch, P., Rose‐John, S., Kress, M. Impaired mechanical, heat, and cold nociception in a murine model of genetic TACE/ADAM17 knockdown. FASEB J. 33, 4418–4431 (2019). www.fasebj.org